Bruno Schulz w ’Umarłej klasie’ Tadeusza Kantora. Realność artystyczna i koneksje literackie - Flader-Rzeszowska, Katarzyna (Załącznik Kulturoznawczy, 2021)
The inspiration that Tadeusz Kantor drew from the works by Schulz can be seen in many of his theatre performances. Like he did with Gombrowicz, Kantor never used one specific work to be staged in his theatre. The Dead Class is a piece where one can find influences by Witkacy, Gombrowicz and Schulz – probably the three most important writers for Kantor. In this article, I discuss the way Schulz, with his short story A Pensioner, is handled in the ‘Cricot 2’ performance. Even though many studies concerning this performance have been written and the connections between Kantor and Schulz seem to have been covered, I have not found any study of Dead Class which would indicate any specific references to A Pensioner. In the article, the following questions are explored: Can Schulz’s protagonist be recognized in the senile, childlike old people from Dead Class? Which passages of the short story were used by Kantor? How differently is the notion of death treated in the short story and in the performance? And finally, why – having been so fascinated with The Cinnamon Shops at a young age – did Kantor come back to Bruno Schulz’s writings only as a mature artist? In the article, I also discuss the strategies utilized by Kantor to adapt the non-theatrical prose for the stage.